Routledge Handbook of Civil and Uncivil Society in Southeast Asia - Hansson, Eva; Weiss, Meredith L. (Taylor & Francis, 2023)
The Routledge Handbook of Civil and Uncivil Society in Southeast Asia explores the nature and implications of civil society across the region, engaging systematically with both theoretical approaches and empirical nuance for a systematic, comparative, and informative approach. The handbook actively analyses the varying definitions of civil society, critiquing the inconsistent scrutiny of this sphere over time. It brings forth the need to reconsider civil society development in today's Southeast Asia, including activist organisations' and platforms' composition, claims, resources, and potential to effect sociopolitical change. Structured in five parts, the volume includes chapters written by an international set of experts analysing topics relating to civil society: Spaces and platforms Place within politics Resources and tactics Identity formation and claims Advocacy The handbook highlights the importance of civil society as a domain for political engagement outside the state and parties, across Southeast Asia, as well as the prevalence and weight of 'uncivil' dimensions. It offers a well-informed and comprehensive analysis of the topic and is an indispensable reference work for students and researchers in the fields of Asian Studies, Asian Politics, Southeast Asian Politics and Comparative Politics. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license. Funded by The Research Foundation for State University of New York, USA and The Stockholm Center for Global Asia, Sweden.